Item response theory approach to ethnocentrism - Monaghan, Conal; Bizumic, Boris (Frontiers in Political Science, 2023)
Introduction Although ethnocentrism is one of the fundamental concepts in the social sciences, its study has been impeded by a diversity of conceptualizations and measures. In recent years, a growing number of political scientists and psychologists have undertaken in-depth research into ethnocentrism. In addition, researchers have recently proposed a comprehensive reconceptualization of ethnocentrism and developed a new Ethnocentrism scale. There is strong evidence for this scale's reliability and validity in indexing ethnocentrism, but like most measures in psychology and political science, this scale is based on classical test theory. Item response theory (IRT) is a powerful psychometric technique that can provide a much more sophisticated test of test performance and is currently under-utilized in research. Methods We performed IRT to assess the psychometric properties of the Ethnocentrism scale on a sample of 4,187 participants. Results The scale's items had strong psychometric properties to capture the ethnocentrism latent construct, particularly in the below average to above average range. Men required marginally lower levels of ethnocentrism to endorse less socially acceptable items than women (items relating to superiority, purity, or exploitativeness). When compared to liberals, conservatives responded more readily to nearly all ethnocentrism items. Given this variation, the IRT approach highlighted that future measurements must adjust for differential item functioning, albeit more for political orientation than gender identity. Discussion The findings detail how IRT can enhance measurement in political science and demonstrate the implications for how gender and political ideology may affect the differential performance of items.